2012
DOI: 10.4161/onci.20249
|View full text |Cite
|
Sign up to set email alerts
|

Environment-mediated drug resistance in Bcr/Abl-positive acute lymphoblastic leukemia

Abstract: Although cure rates for acute lymphoblastic leukemia (ALL) have increased, development of resistance to drugs and patient relapse are common. The environment in which the leukemia cells are present during the drug treatment is known to provide significant survival benefit. Here, we have modeled this process by culturing murine Bcr/Abl-positive acute lymphoblastic leukemia cells in the presence of stroma while treating them with a moderate dose of two unrelated drugs, the farnesyltransferase inhibitor lonafarni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 66 publications
(61 reference statements)
2
17
1
Order By: Relevance
“…Inhibitors of Akt and Erk combined respectively with nilotinib diminished resistance. In contrast to our findings, however, inhibition of p38 MAPK in this study increased TKI (nilotinib) resistance [29].…”
Section: Discussioncontrasting
confidence: 99%
“…Inhibitors of Akt and Erk combined respectively with nilotinib diminished resistance. In contrast to our findings, however, inhibition of p38 MAPK in this study increased TKI (nilotinib) resistance [29].…”
Section: Discussioncontrasting
confidence: 99%
“…The tumor microenvironment also plays an important role in drug resistance mechanisms of tumors. Coculture of leukemia cells with stromal cells allows for environment-mediated drug resistance (EMDR) to tyrosine kinase inhibitors (42). This EMDR is associated with differential regulation of inflammation-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis on precursor B-lineage (pre-B) ALL cells from a BCR/ABL transgenic mouse model for Ph-positive ALL undergoing environmental-mediated drug resistance showed significantly increased expression of mRNAs related to stress and inflammation. 6 Among others, we found that transcript levels of the Galectin-3 gene ( Lgals3 ) were significantly increased upon development of resistance to the Bcr/Abl-targeted tyrosine kinase inhibitor nilotinib, and this was also seen in pre-B ALL cells isolated from the BM of BCR/ABL transgenic mice that had been treated with nilotinib for 8 days. 6 …”
mentioning
confidence: 94%
“…6 Among others, we found that transcript levels of the Galectin-3 gene ( Lgals3 ) were significantly increased upon development of resistance to the Bcr/Abl-targeted tyrosine kinase inhibitor nilotinib, and this was also seen in pre-B ALL cells isolated from the BM of BCR/ABL transgenic mice that had been treated with nilotinib for 8 days. 6 …”
mentioning
confidence: 94%